Supramolecular chirality in self-assembled soft materials regulation of chiral nanostructures and chiral functions - Zhang, Li (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.